Being in the zone during physiological birth: a comparative study of hospital and home birth environments - Dahan, Orli; Goldberg, Alon (Frontiers in Global Women's Health, 2025)
IntroductionA flow experience typically occurs when the challenge of a demanding physical activity aligns with an individual's abilities, resulting in a sense of empowerment and fulfillment. Experiencing flow during physiological childbirth occurs in various birth environments, but quantitative studies comparing home birth and hospital birth in this respect are scarce. Childbirth is a psychological, social, and physiological event; thus, the birthing environment probably crucially affects the mental state of birthing women. We hypothesized that home birth will be positively correlated with a heightened flow state experienced by women during physiological labor, differing significantly from the experience of women birthing in a hospital.MethodIsraeli women with physiological childbirth experience were recruited through social media. Participants (n = 421) completed the Flow State Scale (FSS) and a demographic questionnaire.ResultsComparing hospital births and home births, our research reveals a significant correlation between home birth environment and heightened birthing women's flow state. In physiological childbirth, women birthing at home report higher flow states compared to women in hospitals.DiscussionThe observed differences indicate a compelling connection between the birthing environment and the women's experience during labor. The heightened flow state during home births is explained in measured flow dimensions: challenge-skill balance, action-awareness merging, clear goals, unambiguous feedback, concentration, and joy. By comparing correlations of birthing environments and birthing women's flow state, this research contributes a novel perspective to the ongoing discourse on optimizing childbirth experience.